Tinjauan Fenomenologi terhadap Pernikahan Lintas Iman di Dusun Kalibago Desa Kalipang Kecamatan Grogol Kabupaten Kediri - Saiful Mujab (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2018)
This research tries to describe a phenomenon of interreligious marriage in Kalibago-Kalipang village-Grogol district-Kediri regency. Using phenomenology method this project is conducted. This papers is arraged Basend on observation and interview more or less 7 days among several Muslim, Chatolic and Hindus people in there. Finally, the conclution of this research is finding the interesting phenomenon that the harmony relation among some religions while interreligion marriage happen in there. Interreligious marriage does note become a problem and source of conflict. In fact, peope of Kalibago can built an harmony culture on the plurality of religion.